STATUS SOSIAL EKONOMI DAN FERTILITAS: A Latent Variable Approach - Suandi - (PIRAMIDA, 2010)
The main problems faced by developing countries including Indonesia are not onlyeconomic problems that tend to harm, but still met the high fertility rate. The purpose ofwriting to find out the relationship between socioeconomic status to the level of fertilitythrough the "A Latent Variable Approach." The study adopts the approach of fertility oneconomic development. Economic development based on the theories of Malthus: anincrease in "income" is slower than the increase in births (fertility) and is the root ofpeople falling into poverty. However, Becker made linkage model or the influence ofchildren income and price. According to Becker, viewed from the aspect of demand thatthe price of children is greater than the income effect.The study shows that (1) level of education correlates positively on income andnegatively affect fertility, (2) age structure of women (control contraceptives) adverselyaffect fertility. That is, the older the age, the level of individual productivity and lowerfertility or declining, and (3) husband's employment status correlated positively to theearnings (income). Through a permanent factor income or household income referred toas a negative influence on fertility. There are differences in value orientation of childrenbetween advanced society (rich) with a backward society (the poor). The poor, forexample, the value of children is more production of goods. That is, children born moreemphasis on aspects of the number or the number of children owned (quantity), numberof children born by the poor is expected to help their parents at the age of retirement orno longer productive so that the child is expected to assist them in economic, security,and social security (insurance), while the developed (rich) children are moreconsumption value or quality of the child.